MELACAK KONSEP AUTO IMUNISASI AGAMA MENURUT JAQUES DERIDA (Suatu Upaya Menjawab Tantangan Hidup Religius di Era Kontemporer) - Utang, Herman Yoseph (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2023)
Human life is always faced with challenges to change and develop, including religious life in the contemporary era. There is the problem of religious truths being understood narrowly and giving rise to radicalism. Tracing the concept of religious auto-immunization according to Jaques Derida is an attempt to understand the challenges of religious life in the contemporary era. There is an effort to give new meaning to religious life in religions in order to change the perspective and way of religious life in a new context.